The STUDENTS’ PERCEPTIONS ON THE USE OF TEAM-BASED PROJECT IN ENGLISH VOCABULARY LESSON AT SMA MUHAMMADIYAH 1 UNISMUH MAKASSAR: Nurwahidah English Education Departement, Faculty Of Teacher Training And Education Muhammadiyah University Of Makassar, Jl. Sultan Alauddin No 259, Indonesia - Nurwahidah Nurwahidah; Nur Devi Bte Abdul; Andi Asri Jumiaty (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Nurwahidah, 2021. Students’ Perceptions to the Team-Based Project in English Vocabulary Lesson at SMA Muhammadiyah 1 Unismuh Makassar. A Thesis of English Education Department Faculty of Teacher Training and Education, Muhammadiyah University of Makassar.Supervisors: Nurdevi Bte Abdul and Andi Asri Jumiaty.This research aimed to determine how are students' perceptions of the Team-Based Project function in English vocabulary lessons at SMA Muhammadiyah 1 Unismuh Makassar. The subject of this research is 56 students in class XII. The research method used was descriptive qualitative with questionnaires and interviews. The questionnaire aimed to determine students' perceptions of the Team-Based Project by distributing questionnaires in the form of a Google-form via smartphones, and interview was used as supporters in collecting data to determine students' perceptions of the Team-Based Project.The results of the data indicate that, the students give positive perceptions on the use of Team-Based Project. In this case most the students give agree statement on the questionnaire given. Then from the results of interviews, several students said that having a Team-Based Project was very helpful in the learning process, especially in English lessons. It can be concluded that students' perceptions on the use of Team-Based Projects, on the results of questionnaires and student interviews gives positive perceptions to be used in English subjects because they can improve students' self-development and help in the learning process.